Adaptive Recurrent Network Network Uncertainty Observer Based Integral Backstepping Control for a PMSM Drive System - Chih-Hong Lin; Ren-Cheng Wu (Institute of Advanced Engineering and Science, 2012)
The permanent magnet synchronous motor (PMSM) is suitable for high-performance servo applications and has been used widely for the industrial robots, computer-numerically-controlled (CNC) machine tools and elevators. The control performance of the actual PMSM drive system depends on many parameters, such as parameter variations, external load disturbance, and friction force. Their relationships are complex and the actual PMSM drive system has the properties of nonlinear uncertainty and time-varying characteristics. It is difficult to establish an accurate model for the nonlinear uncertainty and time-varying characteristics of the actual PMSM drive system Therefore, an adaptive recurrent neural network uncertainty observer (ARNNUO) based integral backstepping control system is developed to overcome this problem in this paper. The proposed control strategy is based on integral backstepping control combined with RNN uncertainty observer to estimate the required lumped uncertainty. An adaptive rule of the RNN uncertainty observer is employed to on-line adjust the weights of sigmoidal functions by using the gradient descent method and the backpropagation algorithm in according to Lyapunov function. This ARNNUO has the on-line learning ability to respond to the system’s nonlinear and time-varying behaviors. Experimental results are executed to show the control performance of the proposed control scheme.DOI: http://dx.doi.org/10.11591/ijpeds.v2i2.260